Phytochemical profiling and cytotoxic evaluation of Premna serratifolia L. against human liver cancer cell line - Singh C.; Anand S.K.; Tiwari K.N.; Mishra S.K.; Kakkar P. (My University, 2025)
Premna serratifolia L. (Lamiaceae) is a medicinal plant, widely distributed in the tropical and subtropical regions and commonly used in traditional medicine. The current study was focused to evaluate the cytotoxic potential of aqueous extract of root of P. serratifolia (AEPS) against human hepatoblastoma cancer cell line (Hep G2).The yield of the dried extract was 5.8% and used for further studies.Cytotoxic potential of AEPS was analyzed by MTT assay, which exhibits IC50 value 1000 µg/mL after 48 h incubation. Hoechst and AO/EtBr staining, ROS measurement, mitochondrial membrane potential, clonogenic and wound healing assays also confirmed the cytotoxic efficacy of AEPS in dose and time-dependent manner. UPLC–Q-TOF–MS/MS analysis of AEPS confirmed the presence of 12polyphenolic compounds, namely 4-hydroxy-3-methoxycinnamic acid, linarin, peonidin-3,5-O-di-beta-glucopyranoside, diosmin, trans-cinnamic acid, daidzein, saponarin, homoorietin, acacetin, sarsasapogenin, phytol and sissotrin. The cytotoxic potential of AEPS might due to presence of biologically active polyphenolic compounds. © 2021, King Abdulaziz City for Science and Technology.